Sealant for organic electroluminescent display element
By using a curable resin composition containing a cationic polymerizable compound and a cationic polymerization initiator, the problem of the photocurable adhesive ejaculation during light irradiation is solved, and high stability and excellent organic electroluminescent display elements are achieved. Coating properties.
Patent Information
- Application Number
- CN202210362429.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-08-08
- Filing Date
- 2017-08-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2037-08-02
AI Technical Summary
The conventional photocurable adhesive produces gas when light is irradiated, resulting in poor stability and coating properties of the organic electroluminescent display element.
The curable resin composition containing a cationic polymerizable compound and a cationic polymerization initiator is used to inhibit the generation of ejaculation and improve the coating properties through specific compound combinations and proportions.
It has achieved the suppression of the generation of exhaust gas and improved the coating properties of curable resins, and it is suitable for sealants for organic electroluminescent display elements, which improves the stability and durability of the elements.
Smart Images

Figure CN114716648B_ABST
Abstract
Description
[0001] This application is a divisional application. The filing date of the parent application is August 2, 2017. The international application number is PCT / JP2017 / 028025. The application number entering the Chinese national phase is 201780011598.6. The name of the invention is curable resin composition and sealant for organic electroluminescent display elements. Technical Field
[0002] The present invention relates to a curable resin composition which can suppress the generation of outgassing and has excellent coating properties. In addition, the present invention relates to a sealing agent for an organic electroluminescent display element comprising the curable resin composition. Background Art
[0003] In recent years, research on electronic devices using organic thin film elements such as organic electroluminescent display elements (organic EL display elements) and organic thin film solar cell elements has been promoted. Organic thin film elements can be easily produced by vacuum deposition, solution coating, etc., and therefore have excellent productivity.
[0004] The organic EL display element has a thin film structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into the organic light-emitting material layer from one electrode and holes are injected into the organic light-emitting material layer from the other electrode, so that the electrons and holes are combined in the organic light-emitting material layer and emit light. Compared with liquid crystal display elements that require backlight, it has the advantages of good visual recognition, further thinning, and DC low voltage drive.
[0005] However, such organic EL display elements have the problem of rapid deterioration of their luminescent properties and shortened lifespan when the organic luminescent material layer and electrodes are exposed to outdoor air. Therefore, for organic EL display elements, sealing technology that blocks the organic luminescent material layer and electrodes from moisture and oxygen in the atmosphere is essential to improve stability and durability.
[0006] Patent document 1 discloses a method in which, for a top-emitting organic EL display element, a photocurable adhesive is filled between substrates of an organic EL display element, and light is irradiated to seal the surface. However, such conventional photocurable adhesives have the problem of outgassing when irradiated with light, which degrades the element or deteriorates the coating properties.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2001-357973 Summary of the invention
[0010] Problems to be solved by the invention
[0011] An object of the present invention is to provide a curable resin composition that can suppress the generation of outgassing and has excellent coating properties. Another object of the present invention is to provide a sealing agent for an organic electroluminescent display element comprising the curable resin composition.
[0012] Solutions for solving problems
[0013] The present invention is a curable resin composition comprising a cationically polymerizable compound and a cationic polymerization initiator, wherein the cationically polymerizable compound comprises at least one selected from the group consisting of a compound represented by the following formula (1-1), a compound represented by the following formula (1-2), and a compound represented by the following formula (1-3).
[0014] [Chemistry 1]
[0015]
[0016] In formula (1-1), R 1 is a bond, a linear or branched alkylene group having 1 to 18 carbon atoms, or a linear or branched alkenylene group having 2 to 18 carbon atoms; R 2 and R 3 are each independently hydrogen or a linear or branched alkyl group having 1 to 18 carbon atoms. 4 is a linear or branched alkylene group having 3 to 18 carbon atoms, or a linear or branched alkenylene group having 3 to 18 carbon atoms; R 5 and R 6 Each independently represents hydrogen or a linear or branched alkyl group having 1 to 18 carbon atoms. 7 and R 8 Each is independently a linear or branched alkylene group having 1 to 18 carbon atoms, or a linear or branched alkenylene group having 2 to 18 carbon atoms; R 9 ~R 12 Each is independently hydrogen or a linear or branched alkyl group having 1 to 18 carbon atoms.
[0017] Hereinafter, the present invention will be described in detail.
[0018] The present inventors have found that by using a specific cationically polymerizable compound, a curable resin composition can be obtained which can suppress the generation of outgassing and has excellent coating properties, thereby completing the present invention.
[0019] The curable resin composition of the present invention contains a cationically polymerizable compound.
[0020] The cationic polymerizable compound contains at least one selected from the group consisting of the compound represented by the above formula (1-1), the compound represented by the above formula (1-2), and the compound represented by the above formula (1-3) (hereinafter also referred to as "the epoxy compound described in the present invention"). By containing the epoxy compound described in the present invention, the curable resin composition of the present invention can suppress the generation of outgassing and has excellent coating properties. In addition, by containing the epoxy compound described in the present invention, the obtained curable resin composition has excellent flexibility after curing, and can also be used for flexible electronic devices.
[0021] From the viewpoint of compatibility with other components and hardness of the cured product, R in the above formula (1-1) 1 , R in the above formula (1-2) 4 , and R in the above formula (1-3) 7 and R 8 It is preferably a linear or branched alkylene group having 1 to 18 carbon atoms, and more preferably a linear or branched alkylene group having 3 to 12 carbon atoms.
[0022] Examples of the compound represented by the formula (1-1) include 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, 1,9-decadiene diepoxide, and 1,11-dodecadiene diepoxide.
[0023] Examples of the compound represented by the formula (1-2) include 1,2-epoxycyclopentane, 1,2-epoxycyclohexane, 1,2-epoxycycloheptane, 1,2-epoxycyclooctane, 1,2-epoxycyclodecane, 1,2-epoxycyclododecane, 1-methyl-1,2-epoxycyclopentane, and 5,6-epoxy-1-cyclooctene.
[0024] Examples of the compound represented by the formula (1-3) include 1,2,5,6-diepoxycyclooctane and the like.
[0025] Examples of commercially available products of the epoxy compound of the present invention include reagents manufactured by Tokyo Chemical Industry Co., Ltd., and the like.
[0026] Among them, the cationically polymerizable compound preferably contains a compound represented by the above formula (1-1), and more preferably contains 1,7-octadiene diepoxide, from the viewpoint that the curability of the obtained curable resin composition and the flexibility after curing are particularly excellent.
[0027] The curable resin composition of the present invention may contain other cationically polymerizable compounds within a range not impairing the object of the present invention.
[0028] Examples of the other cationic polymerizable compounds include compounds having two or more oxidized cycloolefin groups in one molecule, other epoxy compounds such as bisphenol A epoxy resins and bisphenol F epoxy resins, oxetane compounds, vinyl ether compounds, etc. Among them, compounds having two or more oxidized cycloolefin groups in one molecule are preferred, and compounds having two or more oxidized cyclohexenyl groups in one molecule are more preferred, from the perspective of providing a more excellent curability of the resulting curable resin composition.
[0029] Examples of the compound having two or more oxycyclohexenyl groups in one molecule include 3′,4′-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate.
[0030] When the above-mentioned other cationic polymerizable compounds are contained, the preferred lower limit of the content of the epoxy compound described in the present invention is 10 parts by weight and the preferred upper limit is 90 parts by weight in 100 parts by weight of the total cationic polymerizable compound. By making the content of the epoxy compound described in the present invention within this range, the coating property, outgassing suppression effect and flexibility of the obtained curable resin composition become more excellent. The more preferred lower limit of the content of the epoxy compound described in the present invention is 20 parts by weight, the more preferred upper limit is 80 parts by weight, and the further preferred upper limit is 50 parts by weight.
[0031] The curable resin composition of the present invention contains a cationic polymerization initiator.
[0032] Examples of the cationic polymerization initiator include thermal cationic polymerization initiators that generate protonic acids or Lewis acids by heating and photocationic polymerization initiators that generate protonic acids or Lewis acids by light irradiation. The cationic polymerization initiator may be an ionic acid generating type or a nonionic acid generating type.
[0033] As the thermal cationic polymerization initiator, BF4 is preferred. - PF6 - 、SbF6 - or (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) as the counter anion, a sulfonium salt, a phosphonium salt, a quaternary ammonium salt, a diazonium salt or an iodonium salt, and a sulfonium salt is more preferred.
[0034] Examples of the sulfonium salt include triphenylsulfonium boron tetrafluoride, triphenylsulfonium antimony hexafluoride, triphenylsulfonium arsenic hexafluoride, tri(4-methoxyphenyl)sulfonium arsenic hexafluoride, and diphenyl(4-phenylthiophenyl)sulfonium arsenic hexafluoride.
[0035] Examples of the phosphonium salt include ethyltriphenylphosphonium antimony hexafluoride and tetrabutylphosphonium antimony hexafluoride.
[0036] Examples of the quaternary ammonium salt include dimethylphenyl(4-methoxybenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methoxybenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methoxybenzyl)ammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorophosphate, dimethylphenyl(4-methylbenzyl)ammonium hexafluoroantimonate, dimethylphenyl(4-methylbenzyl)ammonium hexafluorotetrakis(pentafluorophenyl)borate, methylphenyldibenzylammonium, and methylphenyl. Dibenzylammonium hexafluoroantimonate hexafluorophosphate, methylphenyldibenzylammonium tetrakis(pentafluorophenyl)borate, phenyltribenzylammonium tetrakis(pentafluorophenyl)borate, dimethylphenyl(3,4-dimethylbenzyl)ammonium tetrakis(pentafluorophenyl)borate, N,N-dimethyl-N-benzylanilinium antimony hexafluoride, N,N-diethyl-N-benzylanilinium boron tetrafluoride, N,N-dimethyl-N-benzylpyridinium antimony hexafluoride, N,N-diethyl-N-benzylpyridinium trifluoromethanesulfonic acid, etc.
[0037] Commercially available products of the thermal cationic polymerization initiators include, for example, San-Aid SI-60, San-Aid SI-80, San-Aid SI-B3, San-Aid SI-B3A, San-Aid SI-B4 (all manufactured by Sanshin Chemical Industries, Ltd.), CXC-1612, CXC-1738, and CXC-1821 (all manufactured by King Industries, Ltd.).
[0038] Examples of the ionic photoacid generating polymerization initiator among the above-mentioned photocationic polymerization initiators include BF4 - PF6 - 、SbF6 - or (BX4) - (wherein X represents a phenyl group substituted with at least two fluorine or trifluoromethyl groups) an aromatic sulfonium salt, an aromatic iodonium salt, an aromatic diazonium salt, an aromatic ammonium salt, or a (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt.
[0039] Examples of the aromatic sulfonium salt include bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(diphenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(diphenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(diphenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, diphenyl-4-(phenylthio)phenylsulfonium hexafluorophosphate, diphenyl-4-(phenylthio)phenylsulfonium hexafluoroantimonate, diphenyl-4-(phenylthio)phenylsulfonium tetrafluoroborate, and diphenyl-4-(phenylthio)phenylsulfonium tetrakis(pentafluorophenyl)borate. triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrafluoroborate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluorophosphate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bishexafluoroantimonate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide bistetrafluoroborate, bis(4-(bis(4-(2-hydroxyethoxy))phenylsulfonium)phenyl)sulfide tetrakis(pentafluorophenyl)borate, and the like.
[0040] Examples of the aromatic iodonium salt include diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, diphenyliodonium tetrafluoroborate, diphenyliodonium tetrakis(pentafluorophenyl)borate, bis(dodecylphenyl)iodonium hexafluorophosphate, bis(dodecylphenyl)iodonium hexafluoroantimonate, bis(dodecylphenyl)iodonium tetrafluoroborate, bis(dodecylphenyl)iodonium tetrakis(pentafluorophenyl)borate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluorophosphate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium hexafluoroantimonate, 4-methylphenyl-4-(1-methylethyl)phenyliodonium tetrakis(pentafluorophenyl)borate, and the like.
[0041] Examples of the aromatic diazonium salt include phenyldiazonium hexafluorophosphate, phenyldiazonium hexafluoroantimonate, phenyldiazonium tetrafluoroborate, and phenyldiazonium tetrakis(pentafluorophenyl)borate.
[0042] Examples of the aromatic ammonium salt include 1-benzyl-2-cyanopyridinium hexafluorophosphate, 1-benzyl-2-cyanopyridinium hexafluoroantimonate, 1-benzyl-2-cyanopyridinium tetrafluoroborate, 1-benzyl-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluorophosphate, 1-(naphthylmethyl)-2-cyanopyridinium hexafluoroantimonate, 1-(naphthylmethyl)-2-cyanopyridinium tetrakis(pentafluorophenyl)borate, and the like.
[0043] Examples of the above-mentioned (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe salt include (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluorophosphate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) hexafluoroantimonate, (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrafluoroborate, and (2,4-cyclopentadien-1-yl)((1-methylethyl)benzene)-Fe(II) tetrakis(pentafluorophenyl)borate.
[0044] Examples of the nonionic photoacid generating polymerization initiator among the photocationic polymerization initiators include nitrobenzyl esters, sulfonic acid derivatives, phosphoric acid esters, phenolsulfonic acid esters, naphthoquinone diazide, and N-hydroxyimidesulfonic acid esters.
[0045] Commercially available products of the above-mentioned photocationic polymerization initiators include, for example, DTS-200 (manufactured by Midori Chemical Co., Ltd.); UVI6990, UVI6974 (both manufactured by Union Carbide Co., Ltd.); SP-150, SP-170 (both manufactured by ADEKA Co., Ltd.); FC-508, FC-512 (both manufactured by 3M Co., Ltd.); IRGACURE290 (manufactured by BASF Co., Ltd.); PI2074 (manufactured by Rhodia Co., Ltd.), etc.
[0046] The polymerization initiators described in both the thermal cationic polymerization initiator and the photocationic polymerization initiator may be used as the thermal cationic polymerization initiator or the photocationic polymerization initiator.
[0047] The preferred lower limit of the content of the cationic polymerization initiator is 0.01 parts by weight and the preferred upper limit is 10 parts by weight relative to 100 parts by weight of the cationic polymerizable compound. By making the content of the cationic polymerization initiator 0.01 parts by weight or more, the curability of the obtained curable resin composition becomes more excellent. By making the content of the cationic polymerization initiator 10 parts by weight or less, the curing reaction of the obtained curable resin composition will not become too fast, the workability becomes better, and the cured product can be made more uniform. The more preferred lower limit of the content of the cationic polymerization initiator is 0.05 parts by weight and the more preferred upper limit is 5 parts by weight.
[0048] The curable resin composition of the present invention may contain a sensitizer. The sensitizer has a function of further improving the polymerization initiation efficiency of the cationic polymerization initiator and further promoting the curing reaction of the curable resin composition of the present invention.
[0049] Examples of the sensitizer include anthracene compounds such as 9,10-dibutoxyanthracene; thioxanthone compounds such as 2,4-diethylthioxanthone; 2,2-dimethoxy-1,2-diphenylethane-1-one, benzophenone, 2,4-dichlorobenzophenone, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, and 4-benzoyl-4'methyldiphenyl sulfide.
[0050] The preferred lower limit of the content of the sensitizer is 0.05 parts by weight and the preferred upper limit is 3 parts by weight relative to 100 parts by weight of the cationic polymerizable compound. By making the content of the sensitizer 0.05 parts by weight or more, the sensitization effect can be further exerted. By making the content of the sensitizer 3 parts by weight or less, the absorption does not become too large, and the light can be propagated to a deep part. The more preferred lower limit of the content of the sensitizer is 0.1 parts by weight, and the more preferred upper limit is 1 part by weight.
[0051] The curable resin composition of the present invention may contain a thermosetting agent. Examples of the thermosetting agent include hydrazide compounds, imidazole derivatives, acid anhydrides, dicyandiamide, guanidine derivatives, modified aliphatic polyamines, and addition products of various amines and epoxy resins.
[0052] Examples of the hydrazide compound include 1,3-bis(hydrazinocarbonylethyl-5-isopropylhydantoin), sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0053] Examples of the imidazole derivatives include 1-cyanoethyl-2-phenylimidazole, N-(2-(2-methyl-1-imidazolyl)ethyl)urea, 2,4-diamino-6-(2'-methylimidazolyl-(1'))-ethyl-s-triazine, N,N'-bis(2-methyl-1-imidazolylethyl)urea, N,N'-(2-methyl-1-imidazolylethyl)adipamide, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and 2-phenyl-4,5-dihydroxymethylimidazole.
[0054] Examples of the acid anhydride include tetrahydrophthalic anhydride and ethylene glycol bis(anhydrotrimellitate).
[0055] These thermosetting agents may be used alone or in combination of two or more.
[0056] Examples of commercially available products of the thermosetting agent include SDH (manufactured by Nippon Fine Chemicals Co., Ltd.); ADH (manufactured by Otsuka Chemical Co., Ltd.); Amicure VDH, Amicure VDH-J, and Amicure UDH (all manufactured by Ajinomoto Fine-Techno Co., Ltd.).
[0057] The preferred lower limit of the content of the above-mentioned thermosetting agent is 0.5 parts by weight and the preferred upper limit is 30 parts by weight relative to 100 parts by weight of the above-mentioned cationic polymerizable compound. By making the content of the above-mentioned thermosetting agent 0.5 parts by weight or more, the thermosetting property of the obtained curable resin composition becomes better. By making the content of the above-mentioned thermosetting agent 30 parts by weight or less, the storage stability of the obtained curable resin composition becomes better, and the moisture resistance of the cured product becomes better. The more preferred lower limit of the content of the above-mentioned thermosetting agent is 1 part by weight, and the more preferred upper limit is 15 parts by weight.
[0058] The curable resin composition of the present invention may contain a stabilizer for the purpose of improving storage stability and the like.
[0059] Examples of the stabilizer include amine compounds such as benzylamine and aminophenol-type epoxy resins.
[0060] The preferred lower limit of the content of the stabilizer is 0.001 parts by weight and the preferred upper limit is 2 parts by weight relative to 100 parts by weight of the cationic polymerizable compound. By making the content of the stabilizer within this range, the effects of suppressing curing hindrance and improving the storage stability of the obtained curable resin composition are more excellent. The more preferred lower limit of the content of the stabilizer is 0.05 parts by weight and the more preferred upper limit is 1 part by weight.
[0061] The curable resin composition of the present invention may contain a silane coupling agent. The silane coupling agent has a function of improving the adhesion between the curable resin composition of the present invention and a substrate or the like.
[0062] Examples of the silane coupling agent include 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, and 3-isocyanatepropyltrimethoxysilane. These silane coupling agents may be used alone or in combination of two or more.
[0063] The preferred lower limit of the content of the silane coupling agent is 0.1 parts by weight and the preferred upper limit is 10 parts by weight relative to 100 parts by weight of the cationic polymerizable compound. By making the content of the silane coupling agent within this range, the effect of suppressing the oozing out caused by the excess silane coupling agent and improving the adhesion of the obtained curable resin composition becomes more excellent. The more preferred lower limit of the content of the silane coupling agent is 0.5 parts by weight and the more preferred upper limit is 5 parts by weight.
[0064] The curable resin composition of the present invention may contain a surface modifier within a range that does not impair the purpose of the present invention. By containing the surface modifier, the flatness of the coating film of the curable resin composition of the present invention can be improved.
[0065] Examples of the surface modifier include surfactants and leveling agents.
[0066] Examples of the surface modifier include silicone-based, acrylic-based, and fluorine-based surface modifiers.
[0067] Examples of commercially available products of the surface modifiers include BYK-300, BYK-302, and BYK-331 (all manufactured by BYK Chemie Japan Co., Ltd.); UVX-272 (manufactured by Kusumoto Chemicals Co., Ltd.); and Surflon S-611 (manufactured by AGC Seimi Chemical Co., Ltd.).
[0068] The curable resin composition of the present invention may contain a compound or an ion exchange resin that reacts with an acid generated in the curable resin composition in order to improve the durability of the device electrode, within a range not impairing the object of the present invention.
[0069] Examples of the compound that reacts with the generated acid include substances that neutralize with the acid, such as carbonates or hydrogen carbonates of alkali metals, or carbonates or hydrogen carbonates of alkaline earth metals, etc. Specifically, for example, calcium carbonate, calcium hydrogen carbonate, sodium carbonate, sodium hydrogen carbonate, etc. can be used.
[0070] As the ion exchange resin, any of cation exchange type, anion exchange type, and zwitterion exchange type resins can be used, and cation exchange type or zwitterion exchange type resins that can adsorb chloride ions are particularly preferred.
[0071] The sealing agent for an organic EL display element of the present invention preferably contains no solvent, because residual solvent may cause problems such as degradation of the organic light-emitting material layer and generation of outgassing.
[0072] When a solvent is used for adjusting the viscosity or the like, the content of the solvent is preferably 1% by weight or less, more preferably 0.1% by weight or less.
[0073] Furthermore, the curable resin composition of the present invention may contain various known additives such as a curing retardant, a reinforcing agent, a softener, a plasticizer, a viscosity modifier, an ultraviolet absorber, an antioxidant, and a desiccant as necessary within a range not impairing the purpose of the present invention.
[0074] Examples of a method for producing the curable resin composition of the present invention include a method of mixing a cationically polymerizable compound, a cationic polymerization initiator, and additives such as a silane coupling agent added as needed using a mixer such as a homodispersor, a homomixer, a universal mixer, a planetary mixer, a kneader, or a three-roll mill.
[0075] The lower limit of the overall viscosity of the curable resin composition of the present invention, measured using an E-type viscometer at 25°C and 50 rpm, is 5 mPa·s, and the upper limit is 200 mPa·s. By making the above-mentioned viscosity within this range, the inkjet coating property of the obtained curable resin composition becomes more excellent, and it is more suitable as an in-plane sealant for an organic EL display element. The more preferred lower limit of the above-mentioned viscosity is 8 mPa·s, and the more preferred upper limit is 30 mPa·s.
[0076] The curable resin composition of the present invention is suitable for use in sealing, bonding, coating, etc. of electronic devices, and is more suitable as a sealant for electronic devices, and is particularly suitable as a sealant for organic EL display elements.
[0077] Furthermore, a sealing agent for an organic EL display element containing the curable resin composition of the present invention is also one of the present invention.
[0078] Effects of the Invention
[0079] According to the present invention, a curable resin composition that can suppress outgassing and has excellent coating properties can be provided. In addition, according to the present invention, a sealing agent for an organic electroluminescent display element containing the curable resin composition can be provided. DETAILED DESCRIPTION
[0080] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0081] (Examples 1 to 9, Comparative Examples 1 to 5)
[0082] According to the mixing ratios described in Tables 1 and 2, the respective materials were uniformly stirred and mixed at a stirring speed of 3000 rpm using a homomixer type stirring mixer (manufactured by PRIMIX, "HOMODISPER L type") to prepare curable resin compositions of Examples 1 to 9 and Comparative Examples 1 to 5.
[0083] <Evaluation>
[0084] The curable resin compositions obtained in the Examples and Comparative Examples were evaluated as follows.
[0085] (1) Viscosity
[0086] The viscosity of each curable resin composition obtained in Examples and Comparative Examples was measured under the conditions of 25° C. and 50 rpm using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., “VISCOMETER TV-22”).
[0087] (2) Coating properties
[0088] 0.1 mL of each curable resin composition obtained in the examples and comparative examples was applied to a glass substrate using a pipette, and the diameter expanded after 1 minute was measured. The coating properties were evaluated by recording the diameter as "◎" for a diameter of 15 mm or more, "○" for a diameter of 12 mm or more and less than 15 mm, "△" for a diameter of 10 mm or more and less than 12 mm, and "×" for a diameter of less than 10 mm.
[0089] (3) Curing
[0090] Each of the curable resin compositions obtained in the examples and comparative examples was irradiated with an ultraviolet ray device ("QEL-15SQ3W" manufactured by Quark Technology) at a temperature of 1500 mJ / cm 2 The curing was performed by irradiating ultraviolet rays at 395 nm. The heat release before and after curing was measured using a DSC device (manufactured by RIGAKU, "Thermo Plus 2 / DSC8230"), and the reaction rate of the epoxy group was derived from the following formula. It should be noted that the curable resin composition obtained in Example 8 was cured by heating at 100°C for 30 minutes instead of ultraviolet irradiation.
[0091] Reaction rate of epoxy group (%) = 100 × (heat release before curing - heat release after curing) / heat release before curing
[0092] The curability was evaluated by marking the case where the reaction rate of the epoxy group was 95% or more as "◎", the case where the reaction rate was 90% or more and less than 95% as "○", the case where the reaction rate was 70% or more and less than 90% as "△", and the case where the reaction rate was less than 70% as "×".
[0093] It should be noted that the above-mentioned "heat release before curing" refers to the heat release when the unreacted curable resin composition is reacted and completely cured by heating at a high temperature, and the above-mentioned "heat release after curing" refers to the heat release generated by the reaction of the residual functional groups of the curable resin composition after curing.
[0094] (4) Softness
[0095] Each curable resin composition obtained in Examples and Comparative Examples was sandwiched between two sheets of PET resin at a thickness of 100 μm and irradiated with an ultraviolet ray device (manufactured by Quark Technology, “QEL-15SQ3W”) at a rate of 1500 mJ / cm 2The curable resin composition was cured by irradiating ultraviolet rays at 395 nm to prepare a test film having a thickness of 100 μm. The curable resin composition obtained in Example 8 was cured by heating at 100° C. for 30 minutes instead of irradiating with ultraviolet rays to prepare a test film.
[0096] When the obtained test film was bent to a curvature of 1 cm in diameter, the case where the resin film was not broken was marked as "○", and the case where the resin film was broken was marked as "×", and the flexibility was evaluated.
[0097] (5) Low outgassing
[0098] 100 mg of each curable resin composition obtained in Examples and Comparative Examples was measured and sealed in a vial, and an ultraviolet irradiation device (manufactured by Quark Technology, "QEL-15SQ3W") was used to irradiate the mixture at 1500 mJ / cm 2 The curable resin composition was cured by irradiating ultraviolet rays of 395 nm. The vial was then heated in a constant temperature oven at 85° C. for 100 hours, and the vaporized components in the vial were measured using a gas chromatograph-mass spectrometer (manufactured by JEOL Ltd., “JMS-Q1050”). It should be noted that the curable resin composition obtained in Example 8 was cured by heating at 100° C. for 30 minutes instead of ultraviolet irradiation.
[0099] The low outgassing property was evaluated by marking “○” when the amount of vaporized components was less than 50 ppm, “△” when the amount of vaporized components was 50 ppm or more and less than 100 ppm, and “×” when the amount of vaporized components was 100 ppm or more.
[0100] (6) Display performance of organic EL display elements
[0101] (Preparation of a substrate having a laminate having an organic light-emitting material layer)
[0102] On a glass substrate (length 30 mm, width 30 mm, thickness 0.7 mm) The ITO electrode was formed into a film with a thickness of 1000 nm as a substrate. The substrate was ultrasonically cleaned with acetone, alkaline aqueous solution, ion exchange water, and isopropyl alcohol for 15 minutes, and then cleaned with boiled isopropyl alcohol for 10 minutes, and then pre-treated with a UV-ozone cleaner (manufactured by Japan Laser Electronics Co., Ltd., "NL-UV253").
[0103] Next, the substrate was fixed to the substrate holder of the vacuum deposition device, 200 mg of N,N'-di(1-naphthyl)-N,N'-diphenylbenzidine (α-NPD) was added to a bisque-fired crucible, 200 mg of tri(8-hydroxyquinoline)aluminum (Alq3) was added to another bisque-fired crucible, and the vacuum chamber was depressurized to 1×10 -4 Pa. Then, the crucible filled with α-NPD was heated to make α-NPD The deposition rate is deposited on the substrate, and the film thickness is Next, the crucible filled with Alq3 is heated to The deposition rate is the film thickness Then, the substrate with the hole transport layer and the organic light emitting material layer was transferred to another vacuum evaporation device, 200 mg of lithium fluoride was added to a tungsten resistance heating boat in the vacuum evaporation device, and 1.0 g of aluminum wire was added to another tungsten boat. Then, the pressure in the evaporator of the vacuum evaporation device was reduced to 2×10 -4 Pa, The evaporation rate of lithium fluoride is After that, The aluminum film is formed at a speed of The pressure inside the vapor deposition device was returned to normal pressure using nitrogen gas, and the substrate on which the laminated body having the organic light-emitting material layer was arranged was taken out.
[0104] (Coating with Inorganic Material Film A)
[0105] A mask having an opening is provided in the obtained substrate on which the laminate is arranged so as to cover the entire laminate, and an inorganic material film A is formed by a plasma CVD method.
[0106] The plasma CVD method is carried out under the following conditions: SiH4 gas and nitrogen gas are used as raw material gases, the respective flow rates are set to 10 sccm for SiH4 gas and 200 sccm for nitrogen, the RF power is set to 10 W (frequency 2.45 GHz), the temperature in the chamber is set to 100°C, and the pressure in the chamber is set to 0.9 Torr.
[0107] The thickness of the formed inorganic material film A was about 1 μm.
[0108] (Formation of resin protective film)
[0109] An inkjet ejection device (manufactured by MICROJET, "NANOPRINTER300") was used to apply each curable resin composition obtained in the Examples and Comparative Examples to a glass substrate by inkjet method at an ejection volume of 80 pL. The coating was adjusted so that the film thickness was 20 μm or less. Then, an ultraviolet irradiation device (manufactured by Quark Technology, "QEL-15SQ3W") was used at 1500 mJ / cm 2 The curable resin composition was irradiated with ultraviolet rays of 395 nm and then cured by heating at 80° C. for 30 minutes to form a resin protective film. The curable resin composition obtained in Example 8 was cured by heating at 100° C. for 30 minutes instead of ultraviolet irradiation.
[0110] (Coating with Inorganic Material Film B)
[0111] After forming the resin protective film, a mask having an opening is provided so as to cover the entire resin protective film, and an inorganic material film B is formed by a plasma CVD method, thereby obtaining an organic EL display element.
[0112] The plasma CVD method is carried out under the following conditions: SiH4 gas and nitrogen gas are used as raw material gases, the respective flow rates are set to 10 sccm for SiH4 gas and 200 sccm for nitrogen, the RF power is set to 10 W (frequency 2.45 GHz), the temperature in the chamber is set to 100°C, and the pressure in the chamber is set to 0.9 Torr.
[0113] The thickness of the formed inorganic material film B was about 1 μm.
[0114] (Light Emitting State of Organic EL Display Element)
[0115] After the obtained organic EL display element was exposed to the conditions of temperature 85°C and humidity 85% for 100 hours, a voltage of 10V was applied, and the luminous state of the element (presence of luminescence and dark spots) was observed visually. The situation of no dark spots, peripheral extinction, and uniform luminescence was recorded as "○"; the situation of confirmed dark spots and peripheral extinction was recorded as "△"; the situation of significant expansion of the non-luminous part was recorded as "×", and the evaluation was carried out.
[0116] [Table 1]
[0117]
[0118] [Table 2]
[0119]
[0120] Industrial Applicability
[0121] According to the present invention, a curable resin composition that can suppress outgassing and has excellent coating properties can be provided. In addition, according to the present invention, a sealing agent for an organic electroluminescent display element containing the curable resin composition can be provided.
Claims
1. A sealant for an organic electroluminescent display element, characterized in that: It comprises a curable resin composition containing a cationically polymerizable compound and a cationic polymerization initiator, wherein: The cationically polymerizable compound includes a compound represented by the following formula (1-2): In formula (1-2), R 4 is a linear or branched alkylene group having 3 to 18 carbon atoms, or a linear or branched alkenylene group having 3 to 18 carbon atoms; R 5 and R 6 are each independently hydrogen or a linear or branched alkyl group having 1 to 18 carbon atoms, The cationically polymerizable compound further contains other cationically polymerizable compounds, The content of the compound represented by the formula (1-2) is 10 parts by weight or more and 90 parts by weight or less in 100 parts by weight of the total cationically polymerizable compound.
2. The sealant for an organic electroluminescent display element according to claim 1, wherein The other cationically polymerizable compound contains at least one selected from the group consisting of a compound having two or more oxycycloolefin groups in one molecule, a bisphenol A epoxy resin, a bisphenol F epoxy resin, an oxetane compound, and a vinyl ether compound. 3 . The sealant for an organic electroluminescent display element according to claim 1 , wherein the curable resin composition has a viscosity of 5 mPa·s or more and 200 mPa·s or less measured at 25° C. and 50 rpm using an E-type viscometer.
Citation Information
Patent Citations
Display device
JP2001357973A
Energy ray-curable resin composition and cured product thereof
CN104470971A
Ultraviolet-curing adhesive and attached body using the same
JP2005146038A
Energy sensitive composition, cured article and manufacturing method of cured article
JP2017179330A